The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0034-7167-2019-0825
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of educational technology to prevent complications in intestinal ostomies / periestomy skin

Abstract: Objective: To build and validate an educational booklet for preventing complications in intestinal ostomy and peristomy skin. Methods: Methodological study developed in: 1. Survey of the clinical profile of patients; 2. Integrative review; 3. Construction of technology; 4. Validation of educational material. The Delphi technique was used, with 18 judges with expertise in the field of stomatherapy. For data treatment, the Collective Subject Discourse (CSD), descriptive analysis, Kappa Index (K), binomial test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
1
0
0
11
Order By: Relevance
“…It was observed that the lowest score was in subitem 1.3. This result is in line with other validation studies of educational technologies 21 , probably due to the more colloquial writing style present in the technology to the detriment of scientific terms present in academia. As the product will be indicated for use by the population, even with some adjustments in the information provided, it was decided to keep the simple and colloquial language directed to its target audience.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that the lowest score was in subitem 1.3. This result is in line with other validation studies of educational technologies 21 , probably due to the more colloquial writing style present in the technology to the detriment of scientific terms present in academia. As the product will be indicated for use by the population, even with some adjustments in the information provided, it was decided to keep the simple and colloquial language directed to its target audience.…”
Section: Discussionsupporting
confidence: 91%
“…alergias aos cremes-barreira e placa protetora; e em especial a ausência do conhecimento da pessoa submetida ao processo de estomia (26) .…”
Section: Cuidado àS Pessoas Adultas Com Estomias Deunclassified
“…Sendo assim, é de suma importância que o profissional responsável por realizar o acompanhamento deixe isso bem claro, disponibilizando, se possível, um material que auxilie o cliente ostomizado a como prosseguir, visando o autocuidado eficaz, além, de prevenir futuras complicações. Esse processo deve ser bem orientado, pois, apesar de estressante, torna-se muito necessário 1,2,4,6,9,11,13,14 .…”
unclassified
“…Os profissionais devem conhecer os aspectos clínicos e anatômicos da ostomia, principalmente dos indivíduos atendidos dentro das unidades de assistência à saúde, para que tenham segurança na implantação de protocolos, em busca da oferta assistencial de qualidade e estímulos ao autocuidado desse paciente. As complicações Brazilian Journal of Health Review, Curitiba, v. 6, n. 6, p. 32966-32980, nov./dec., 2023 clínicas e déficits de comunicação são problemas frequentes relacionados à assistência ao paciente, que, em muitos casos, favorecem a evasão do ambiente onde ele deveria ser bem assistido e acabam por vezes em condições piores do que quando entrou 2,3,6,11,13,15,17 .…”
unclassified